An Invitation on Behalf of the Dry Cleaner - Dow Chemical Company (1940)
Color photograph advertisement depicts a woman in a dress holding a dance card making eye contact with a man whose backside can be seen bordering the left side of the photograph. The accompanying text describes how Dow's contributions to the dry cleaning industry, including with the use of Dowclene solvents, enables one to enjoy events involving an invitation by preparing your wardrobe using Dow Chemicals in the dry cleaning process.
Keywords: Chemical industry; Dow Chemical Company; Dance cards; Corporations; Advertising; Dry cleaning industry